(untitled) (Fiep Bulletin - online, 2015)
Cumulative Trauma Disorders (CTD) are, nowadays, considered epidemics and must be studied, prevented and treated by a multiprofessional group. They affect any person submitted to specific work conditions, mainly when repetitive activities, incorrect position, excess of force, physical overload and an inadequate ergonomic work environment are present, and enclose about 30 illnesses related to disturbances in tendons, joints, muscles and nerves. Among these conditions, tendinitis, tenosynovitis and bursitis are the most known. The present study aims to analyze conceptual, legal and clinical aspects of the pathologies present in cumulative trauma disorders cases, enhancing the importance of the physical education professional’s preventive performance on the implement of labor gymnastics programs, and also to assess the gaps in characterization and inclusion of this professional in the normative contents of current Brazilian legislation. This is a qualitative study, with documentary format, in which was used the content analysis technique. The assessment of legal documents containing the clinical, preventive and therapeutic procedures applied to cumulative trauma disorders allowed the conclusion that in none of them the role that physical education professional must perform in the development of preventive actions related to cumulative trauma disorders is determined. Thus, there must be a mayor awareness and professional mobilization in order to revert this important mistake.